2017
DOI: 10.32831/jik.v6i1.154
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Predisposisi Yang Mempengaruhi Keberhasilan Pemberian Asi Eksklusif Berdasarkan Teori Maternal Role Attainment Ramona T Mercer

Abstract: According to the Indonesian Demographic Health Survey (SDKI) from 1997 to 2002, the number of exclusive breastfeeding infants aged six months decreased from 7.9% to 7.8%. Meanwhile, the results of SDKI 2007 showed decreased number of exclusively breastfeeding infants up to 7.2% and the number of infants under six months who fed formula improved from 16.7% in 2002 to 27.9% in 2007. The number of infants in Indonesia who get exclusive breastfeeding continues to decline as more and more babies under 6 months of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Mother's knowledge about breastfeeding is one of the determining factors for the success of mothers in breastfeeding their babies. In their research, Rahayu and Yunarsih [6] reported that factors related to the practice of exclusive breastfeeding were the mother's level of education, information on how to breastfeed, and support from the community. This shows that the community is one of the mothers' peers, which has an influence on the success of exclusive breastfeeding.…”
Section: The Results Of Riskesdas (Basic Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother's knowledge about breastfeeding is one of the determining factors for the success of mothers in breastfeeding their babies. In their research, Rahayu and Yunarsih [6] reported that factors related to the practice of exclusive breastfeeding were the mother's level of education, information on how to breastfeed, and support from the community. This shows that the community is one of the mothers' peers, which has an influence on the success of exclusive breastfeeding.…”
Section: The Results Of Riskesdas (Basic Healthmentioning
confidence: 99%
“…Peer counseling conducted by fellow postpartum mothers about breastfeeding is a means that can be used to increase knowledge and experience in order to achieve breastfeeding success. In a peer or group, mothers can share knowledge and experiences with each other, so that this condition can increase mothers' understanding of effective breastfeeding [6]. By telling their problems to counselors and other postpartum mothers, they are required to be open in revealing information about themselves, their feelings, and their experiences when experiencing these problems [23].…”
Section: Resultsmentioning
confidence: 99%
“…Dalam kurun waktu 2 tahun, adakalanya ibu mengalami beberapa masalah dalam pemberian ASI pada bayinya seperti ketidaklancaran produksi ASI (Rahayu, 2017). Beberapa ibu cemas dan beranggapan bahwa ASI yang diproduksi sedikit atau tidak keluar.…”
Section: Pendahuluanunclassified
“…Untuk meningkatkan keberhasilan pemberian ASI Eksklusif sebaiknya dilakukan penyuluhan dimulai dari kunjungan antenatal ibu hamil yang bertujuan untuk memberikan informasi persiapan pemberian ASI, dan penyuluhan akan dilanjutkan selama pemberian ASI yang bertujuan untuk memantau pemberian ASI Eksklusif hingga 6 bulan dan meningkatkan partisipasi ibu hamil. orang tua dalam kelompok pendukung pemberian ASI eksklusif (Rahayu & Yunarsih, 2017).…”
Section: Peran Besar Atasan Dalam Pemberian Asi Eksklusif Pada Ibu Be...unclassified